2020
DOI: 10.1002/adtp.202000085
|View full text |Cite
|
Sign up to set email alerts
|

Selective Autophagy Pathway of Nanoparticles and Nanodrugs: Drug Delivery and Pathophysiological Effects

Abstract: Research attention has been given to selective autophagy due to its potential application in the pathophysiology of human diseases. The selective autophagy pathway contributes to the target recognition and degradation of intracellular components or foreign pathogens for maintaining cellular homeostasis in multiple organisms. Notably, this process is mediated by autophagy receptors in the recognition of autophagy cargoes through binding to the ubiquitin‐binding domain and LC3‐interacting region to the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 271 publications
(442 reference statements)
0
6
0
Order By: Relevance
“…We reported that ubiquitin decorated NDs bind to autophagy receptors to form nanoparticulosomes for entry into lysosomes and selective autophagy pathway [ 63 ]. The processing of nanoparticles can be through the selective autophagy pathways also called nanoparticulophagy for entering lysosomes [ 64 ]. We suggest that the high specificity of ND-Cet binding to EGFR of lung cancer cells and the EGFR proteins can be transported to lysosome for degradation by the nanoparticulophagy pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that ubiquitin decorated NDs bind to autophagy receptors to form nanoparticulosomes for entry into lysosomes and selective autophagy pathway [ 63 ]. The processing of nanoparticles can be through the selective autophagy pathways also called nanoparticulophagy for entering lysosomes [ 64 ]. We suggest that the high specificity of ND-Cet binding to EGFR of lung cancer cells and the EGFR proteins can be transported to lysosome for degradation by the nanoparticulophagy pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles enter cells via endocytosis or other uptake routes. Nanoparticles colocalize with autophagy receptors or markers to produce nanoparticle-containing autophagosomes called nanoparticulosomes [ 70 ]. These ubiquitinated nanoparticles engage with autophagy receptor proteins, SQSTM1 bound to LC3, forming an autophagosome ( Figure 5 ) [ 70 ].…”
Section: Targeting Autophagy Modulation To Eliminate Environmental Su...mentioning
confidence: 99%
“…Nanoparticles colocalize with autophagy receptors or markers to produce nanoparticle-containing autophagosomes called nanoparticulosomes [ 70 ]. These ubiquitinated nanoparticles engage with autophagy receptor proteins, SQSTM1 bound to LC3, forming an autophagosome ( Figure 5 ) [ 70 ]. Nanoparticles affect autophagy by increasing autophagosome production and flux or causing autophagic malfunction [ 71 ].…”
Section: Targeting Autophagy Modulation To Eliminate Environmental Su...mentioning
confidence: 99%
“…4−6 Selective autophagy is largely activated by exposure to nanoparticles and nanodrugs, indicating that the selective autophagy pathway may be a subcellular target of nanoparticles or nanodrugs. 3,7,8 Nanoparticulophagy is a selective autophagy pathway for processing nanoparticles and nanodrugs and may be an important mechanism in regulating drug delivery and biological effects. Selective autophagy relies on the recognition and degradation of various autophagic substrates or cargos.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing application of nanodrugs in cancer therapy and diagnosis has raised concerns about their pathophysiological effects. Selective autophagy is a highly conserved process for the sequestration and transport of macromolecules and organelles to the lysosome for degradation. Selective autophagy is largely activated by exposure to nanoparticles and nanodrugs, indicating that the selective autophagy pathway may be a subcellular target of nanoparticles or nanodrugs. ,, Nanoparticulophagy is a selective autophagy pathway for processing nanoparticles and nanodrugs and may be an important mechanism in regulating drug delivery and biological effects. , …”
Section: Introductionmentioning
confidence: 99%